Disparitas Pola Konsumsi Pangan Penduduk di Provinsi Banten - Bohari Bohari; Muhammad Ansori; Fachruddin Perdana; Rukman Abdullah (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Food problems arise from a lack of food diversity, high food prices, and a food culture that does not support an adequate supply of nutrients in the household. This study aimed to analyze the disparity of food consumption patterns of the population of Banten Province based on the typology of the region and the administrative area of Banten Province. The research method was an explorative study with a retrospective study approach using secondary data, namely the National Socio-Economic Survey (Susenas) Banten Province 2017. This type of data was collected on the food consumption of the population presented in the form of a table of the average quantity of food consumption per commodity in household order units per capita / week. Data analysis was carried out quantitatively by descriptive methods. The results of the study, namely the quantity of food consumption of the population of Banten Province, showed a disparity based on regional typology where the average energy consumption of food for households in rural areas was still higher, namely 2404 Kcal compared to urban areas, which was 2338 Kcal and was dominated by food sources of grains. The average energy consumption of the population in the regency area is 2315 - 2489 kcal/capita/day while the urban area is 2294 – 2406 kcal/capita/day. The conclusion is that the districts with the highest levels of energy consumption and adequacy are found in Lebak and Pandeglang districts but have the lowest PPH scores compared to other districts.